2020
DOI: 10.1111/jam.14589
|View full text |Cite
|
Sign up to set email alerts
|

Amount of Eurotium sp. in Chinese Liupao tea and its relationship with tea quality

Abstract: Objective Eurotium sp. are the sexual states of the genus Aspergillus, and their ascospore is a spherical closed capsule with a golden colour. The growth of Eurotium sp. during tea production is a key step in achieving the unique quality of dark tea. This study aimed to evaluate the relationship between Eurotium sp. amount and Liupao tea quality. Methods and Results The amounts of Eurotium sp. in 26 differently aged Liupao tea samples from several factories were studied. Indicators related to the quality of Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…These esters were dominated by methyl salicylate and ethyl acetate. Methyl salicylate imparts the aroma of wintergreen oil and mint and has been reported to be one of the key VOCs contributing to the characteristic flavor of FBT samples ( Li et al, 2020a , 2020b ). Notably, organic acids were present at low levels in all FBT samples.…”
Section: Resultsmentioning
confidence: 99%
“…These esters were dominated by methyl salicylate and ethyl acetate. Methyl salicylate imparts the aroma of wintergreen oil and mint and has been reported to be one of the key VOCs contributing to the characteristic flavor of FBT samples ( Li et al, 2020a , 2020b ). Notably, organic acids were present at low levels in all FBT samples.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zhao et al reported that Aspergillus produced a variety of enzymes (pectinesterase, endo-1,4-β-xylanase, catalases, catalase-peroxidases, alkaline protease, and peroxiredoxins) that contributed to the oxidation of tea polyphenols and degradation of plant cell wall ( 30 ). Furthermore, the genus Aspergillus make great contribution to the enhancement of taste by secreting enzymes like proteases, α-amylases glucoamylases, xylanases, and other hemicellulose to decompose complex carbohydrates, proteins and lipid into small molecules in FBT and produce unique flavor ( 31 , 32 ). Besides, it was found that Saccharomycopsis and Debaryomyces were more abundant in the ZJ sample than that in other regions, and Monascus and Wallemia were the two genera that only existed in the ZJ sample.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the amount of Eurotium sp. plays a vital role in developing the unique quality of Liupao tea [ 46 ]. As described by Li [ 47 ], Aspergillus can change the volatile profiles of Liupao tea.…”
Section: Discussionmentioning
confidence: 99%